PENGARUH FAKTOR DEMOGRAFI DAN KEADAAN SOSIAL EKONOMI TERHADAP PENERAPAN SISTEM E-FILLING - Septa Aryani, Dwi (Universitas Muhammadiyah Palembang, 2018)
Since 2014 an e-filling system had been launched by the Directorate General of Taxation. Inorder that e-filling system can be used by the taxpayer, it is necessary to know the factorsthat can affected personal taxpayers in implementing the e-filling system. The purpose of thisresearch is to know how much the influenced of age, education level, and income of taxpayerto applied the e-filling system. Result of the research are; Partially, age (X1) and educationlevel (X2) shown positive and significant influenced on the application of e-filling (Y).Meanwhile, income (X3) doesn’t significantly affected the application of e-filling (Y).Simultaneously; age (X1), education level (X2), and income (X3) were positively andsignificantly influence on the application of e-filling (Y). This can be proved by the F testindicating that a significant F value of 0.00 is smaller than the significant level of 0.05. Withthe enactment of e-fiiling system, it is advisable to socialized the individual taxpayers on howto report taxes with e-filling, to facilitate taxpayers in reporting their tax returns.